1990
DOI: 10.1254/jjp.54.325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ceruletide, Administered Singly and in Combination with Central-Acting Drugs, on Discrete Shuttle Avoidance Response in Mice

Abstract: Abstract-The single administration of ceruletide at 10-300 '"g/kg, i.p., slightly but significantly decreased the response rate (frequency of shuttles) under a discrete avoidance task in mice. Over 10 ag/kg of ceruletide attenuated the increase in the response rate induced by methamphetamine (0.5 mg/kg, s.c.). However, ceruletide, at 1-300 ug/kg, did not significantly enhance the response and/or avoidance-decreasing effects of chlorpromazine (1 mg/kg, s.c.), haloperidol (0.1 mg/kg, s.c.), pilocarpine (4 mg/kg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This re sult indicates the differential characteristics be tween MK-801 and methamphetamine-in duced enhancement of the dopaminergic trans mission. This may be also supported by the facts that ceruletide can completely inhibit the MK-801-induced increase in the mouse's ambulatory activity and the response rate, although it only partially reduced the behavior stimulation by methamphetamine even at large doses (up to 10,ug/kg), and there was no clear dose-effect relationship in the interaction between ceruletide and methamphetamine as demonstrated in the present and previous studies (6,7). MK-801, at 0.1 mg/kg, did not potentiate the stimulant effect of methamphet amine by means of the present avoidance situation and ambulatory activity in mice (un published data, H. Kuribara).…”
supporting
confidence: 78%
See 3 more Smart Citations
“…This re sult indicates the differential characteristics be tween MK-801 and methamphetamine-in duced enhancement of the dopaminergic trans mission. This may be also supported by the facts that ceruletide can completely inhibit the MK-801-induced increase in the mouse's ambulatory activity and the response rate, although it only partially reduced the behavior stimulation by methamphetamine even at large doses (up to 10,ug/kg), and there was no clear dose-effect relationship in the interaction between ceruletide and methamphetamine as demonstrated in the present and previous studies (6,7). MK-801, at 0.1 mg/kg, did not potentiate the stimulant effect of methamphet amine by means of the present avoidance situation and ambulatory activity in mice (un published data, H. Kuribara).…”
supporting
confidence: 78%
“…A preliminary experiment and the previous studies (6,7) demonstrated that the inhibitory action of ceruletide on the ambulation and response-increasing effects of methamphet amine appeared within a few min, and almost the same inhibitory action persisted for longer than 3 hr but not for 24 hr. Therefore, the drug administrations, both in the single and combined administration tests, were conducted immediately before the sessions, and there after the avoidance response of each mouse was observed for 30 min.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…In this study, we further evaluated the characteristics of the CNS stimulant effects of methamphetamine, MK-801 and ketamine through combined administration with the selective dopamine D1 and D2-antagonists SCH 23390 (10,11) and YM-09151-2 (12), respectively, by means of discrete shuttle avoidance in mice. Shuttle avoidance has been empirically considered to be convenient for detect ing both the behavioral stimulant and depressant actions of drugs (13).…”
mentioning
confidence: 99%